Feminist Collections, v.26, no.2-3 (winter-spring 2005) - (:unkn) unknown (My University, 2005)
Subtitle: A Quarterly of Women's Studies Resouces. 42p.
Contents: FROM THE EDITORS. BOOK REVIEWS: Writing and Reading Memoir as Consciousness-Raising: If the Personal Is Political, Is the Memoir Feminist?, by Helen M. Bannan. (En)Gendering Cooking, by Amanda J. Swygart-Hobaugh. Ambiguous Outcomes: Women and the Power and Promise of Medicine, by Judith A. Houck. Blog This!: An Introduction to Blogs, Blogging, and the Feminist Blogosphere and A Sampling of Blogs by Women, for Women, and/or Discussing Women?s Issues, by Vicki Tobias. E-SOURCES ON WOMEN & GENDER. NEW REFERENCE WORKS IN WOMEN'S STUDIES. PERIODICAL NOTES. ITEMS OF NOTE. BOOKS RECENTLY RECEIVED. SUBSCRIPTION FORM.
Keywords: Feminist Blogs; Library Resources; Medicine; Women's Studies; E-Sources; Memoirs; Cooking; Reviews; Gender; Feminism